Digital Television Flexibility: A Survey of Australians with Disability. Issue 1 (February 2014) - Ellis, Katie
Flexibility for many viewers comes from digital technologies and their interaction with television broadcasting. Significantly, as television is switched to digital transmissions, viewers with disability have the potential to experience flexibility in the form of accessibility features such as audio descriptions, captions, lip-reading avatars, signing avatars, spoken subtitles and clean audio. This flexibility may in fact provide some people with access to television for the first time. This exploratory study reports results from an online survey of Australians with disabilities conducted during the final months of the simulcast period before analogue signals were switched off in 2013. While captioning emerged as the most desired accessibility feature, differences surfaced when the data were broken into specific impairment types. This article highlights the importance of digital flexibility specific to impairment type, and locates people with disability as a significant group to consider as more changes take place around digital television broadcasting via the NBN.